The role of compensation management and institutional ownership on tax avoidance - Mulyati, Mulyati; Ferdiansyah, Ferdiansyah (Educoretax, 2025)
This study aims to determine the influence of Management Compensation and Institutional Ownership on Tax Avoidance. This research is a type of quantitative research with a secondary type of data. The source of this research data was obtained from pharmaceutical sector companies listed on the Indonesia Stock Exchange (IDX) for 6 years with a period between 2018 – 2023. The sample selection method used in this study is the purposive sampling method so that the sample obtained with this method is 8 companies. The data used in this study is in the form of annual reports from each company that has been used as a research sample. The analysis technique used was panel data regression analysis with a significance level of 5%. This study was processed using eviews software 12 and showed that (1) management compensation and institutional ownership have a simultaneous effect on tax evasion which means that the hypothesis is accepted (2) management compensation has no significant effect on tax avoidance which means the hypothesis is rejected, and (3) institutional ownership has a significant effect on tax avoidance which means the hypothesis is accepted.